Lab and/or Field? Measuring Personality Processes and Their Social Consequences. Issue 2 (March 2015) - Wrzus, Cornelia; Mehl, Matthias R.
Abstract: How can researchers study personality processes and their social consequences? In our methodology overview, we first introduce ambulatory assessment methods, which repeatedly measure experiences, physiology and behaviour in people's daily lives based on real‐time assessments of self‐reports, physiological activity and behavioural observations. Then, we describe methods suitable for assessing personality processes in laboratory settings: self‐reports on interpersonal perception, physiological measurements and behavioural observation. We discuss the combination of field and laboratory assessment methods based on their respective strengths and limitations and then highlight ethical issues surrounding the use of these methods. Finally, we propose future avenues for how developments in mobile technology can be used to advance personality research. The increasing availability and the decreasing costs of smartphones, wearable sensors and Internet connectivity offer unique potentials for further understanding the processes underlying how personality exerts broad and important social consequences. Copyright © 2015 European Association of Personality Psychology